2015
DOI: 10.1016/j.cgh.2014.10.036
|View full text |Cite
|
Sign up to set email alerts
|

High-dose Dual Therapy Is Superior to Standard First-line or Rescue Therapy for Helicobacter pylori Infection

Abstract: Background & Aims The efficacy of treatment of Helicobacter pylori infection has decreased steadily due to increasing resistance to clarithromycin, metronidazole, and levofloxacin. Resistance to amoxicillin is generally low, and high intragastric pH increases the efficacy of amoxicillin, so we investigated whether a combination of a high-dose proton-pump inhibitor and amoxicillin (dual therapy) was more effective than standard first-line or rescue therapies in eradicating H pylori. Methods We performed a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
283
2
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(298 citation statements)
references
References 34 publications
(52 reference statements)
2
283
2
7
Order By: Relevance
“…amoxicillin dosing) with other regimens as salvage treatments ( 178,203,206 ). Two of these studies have been conducted in Germany, both by Miehlke et al Th e fi rst study included 84 patients with at least one previous treatment failure (most patients had two or more treatment failures) and compared 14-day high-dose dual therapy (omeprazole 40 mg and amoxicillin 750 mg, both given q.i.d .)…”
Section: Clarithromycin Triple Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…amoxicillin dosing) with other regimens as salvage treatments ( 178,203,206 ). Two of these studies have been conducted in Germany, both by Miehlke et al Th e fi rst study included 84 patients with at least one previous treatment failure (most patients had two or more treatment failures) and compared 14-day high-dose dual therapy (omeprazole 40 mg and amoxicillin 750 mg, both given q.i.d .)…”
Section: Clarithromycin Triple Therapymentioning
confidence: 99%
“…By proportion meta-analysis, the pooled eradication rate for high-dose dual salvage treatment in the European studies was 71% (63-79%). Finally, in Taiwan, Yang et al ( 206 ) included 168 patients with one or more previous eradication failures, and reported that the eradication rate with the 14-day high-dose dual therapy (rabeprazole 20 mg and amoxicillin 750 mg, both given q.i.d .) was 89% (81-98%), which was not signifi cantly diff erent than with 7-day levofl oxacin triple therapy (79, 67-90%), but was signifi cantly higher than with 10-day sequential therapy (52, 38-65%).…”
Section: Clarithromycin Triple Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, when the role of high-dose dual therapy (HDDT) with 20 mg RPZ and 750 mg AMPC 4 times per day for 14 days was examined, ITT analysis showed that H. pylori was eradicated in 95.3% of patients in the HDDT group and 81% in the standard triple therapy group [38]. Conversely, a study of the effect of extended dual release LPZ with AMPC had to be discontinued because of a lack of efficacy (53.8% in both ITT and PP analysis) [39].…”
Section: Discussionmentioning
confidence: 99%
“…14,15,19 Newer treatment options, such as concomitant 25,26 (TT plus metronidazole), hybrid 27,28 (ST, but with amoxicillin added during the second half of the regimen) and dual 29 (high dose PPI plus amoxicillin, four doses daily) treatment have been developed, in order to achieve eradication rates > 90%, as defended by Graham et al, 30 and have shown superior eradication rates compared to TT, but in most of them, TT duration was inferior to 14 days. 26,27,29 Regarding ST, a recent meta-analysis comparing it with hybrid and concomitant therapies showed no efficacy advantage in the newer treatment strategies. 31 Bismuth-based regimens, advocated in the Maastricht IV Consensus as a firstline treatment option in regions with high clarithromycin resistance, 1 has shown favorable results, 32 but bismuth is not widely available in many European countries, in particular in Portugal.…”
mentioning
confidence: 99%